Optimum concentration of Bacillus megaterium for strengthening structural concrete - Andalib, R. (Elsevier Ltd, 2016)
Five different cell concentrations of Bacillus megaterium (10 × 105 to 50 × 105 cfu/ml) were introduced in structural concrete to achieve the optimum concentration of bacteria. The significant increase in the strength was obtained in the case of 30 × 105 cfu/ml at different ages. The strength of highest grade of bacterial concrete had improved (24%) as compared to lowest grade (12.8%) due to calcification mechanism. Microbial calcite precipitation was quantified using X-ray diffraction analysis, visualized by scanning electron microscopy and analyzed by energy dispersive spectrometer. It was found that the optimum concentration of B. megaterium had a positive effect on high strength structural concrete.